2019
DOI: 10.1103/physreva.100.032707
|View full text |Cite
|
Sign up to set email alerts
|

Target dependence of postcollision interaction effects on fully differential ionization cross sections

Abstract: We have measured and calculated fully differential cross sections (FDCS) for ionization of helium by 75 keV proton impact. Ejected electron with a speed close to and above the projectile speed were investigated. This range of kinematics represents a largely unexplored regime. A high sensitivity of the FDCS to the details of the description of the few-body dynamics, reported earlier for ionization of H 2 , was confirmed. A new, so far unexplained peak structure was found in an electron angular range between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…To analyze the different effects of each of the terms in the series (7), we have computed different DDCS p for ionization of hydrogen atom by 75-keV proton impact. The results are displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To analyze the different effects of each of the terms in the series (7), we have computed different DDCS p for ionization of hydrogen atom by 75-keV proton impact. The results are displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…. , 5, i.e., the individual DDCS p for m = 0, 1, • • • , 5 have been summed; each result represents the coherent sum of different orders in the transition matrix (7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of these shortcomings are circumvented in distorted wave approaches, e.g., [14][15][16]. However, recently, we demonstrated that in ionization of H 2 and He by intermediate energy proton impact even distorted wave calculations do not give satisfactory results if the electron is ejected with a velocity close to the projectile velocity [17,18].…”
Section: Introductionmentioning
confidence: 99%